Comparative analysis of endogenous hormones level in two soybean (Glycine max L.) lines differing in waterlogging tolerance - Kim, Yoon-Ha; Hwang, Sun-Joo; Waqas, Muhammad; Khan, Abdul L.; Lee, Joon-Hee; Lee, Jeong-Dong; Nguyen, Henry T.; Lee, In-Jung (Frontiers in Plant Science, 2015)
Waterlogged condition due to flooding is one of the major abiotic stresses that drastically affect the soybean growth and yield around the world. Because of this, many breeders have focused on the development of waterlogging tolerance in soybean varieties, and thus, several tolerant varieties were developed. However, the physiological mechanism of waterlogging tolerance is not yet fully understood. We particularly studied the endogenous hormones regulation during waterlogging in two contrasting soybean genotypes. According to our results, adventitious roots better developed in the waterlogging tolerant line (WTL) than in the waterlogging susceptible line (WSL). Endogenous hormones also showed significant differences between WTL and WSL. The ethylene production ratio was higher in WTL than in WSL, and methionine was higher in WTL than in WSL. Other endogenous abscisic acid (ABA) contents were lower in WTL than in WSL. Conversely, gibberellic acid (GA) showed a tendency to be high in WTL, especially the levels of the bioactive GA4. The ratio of total GA and ABA was significantly higher in WTL than in WSL. Anatomical study of the root revealed that aerenchyma cells in the stele were better developed in WTL than in WSL.